Effect of reaction time on structural and magnetic properties of green-synthesized magnetic nanoparticles. (September 2018) - Karade, V.C.; Dongale, T.D.; Sahoo, Subasa C.; Kollu, P.; Chougale, A.D.; Patil, P.S.; Patil, P.B.
Abstract: Fe3 O4 magnetic nanoparticles (MNPs) were prepared using the modified green synthesis method and the effects of reaction time on the structural and magnetic properties of MNPs were evaluated. For the synthesis of MNPs, green tea extract and ethylene glycol were used as a reducing agent and solvent, respectively. The MNPs were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), thermogravimetric analysis and vibrating sample magnetometer. It was observed that the reaction time strongly influenced the magnetic and structural properties. With increasing reaction time, the crystallite size was found to be increased from 7.5 to 12 nm along with improvement in saturation magnetization (MS ). The magnetic measurement study revealed that MNPs were superparamagnetic at room temperature, while at 60 K they have ferromagnetic as well as superparamagnetic contributions. The effect of an increase in particle size with reaction time was also reflected with an increase in blocking temperature, which is consistent with the Stoner–Wohlfarth theory. Highlights: Green synthesis of Fe3 O4 magnetic nanoparticles using green tea extract. Structural and magnetic characterization of Fe3 O4 magnetic nanoparticles. Change in particle size with reaction time.